Wastewater to resource : design of a sustainable phosphorus recovery system - Duan, Menglin (2020)
To enable a more sustainable wastewater treatment processes, a transition towards resource recovery methods that have minimal environmental impact while being financially viable is imperative. Phosphorus (P) is a finite resource that is being discharged into the aqueous environment in excessive quantities. As such, understanding the financial and environmental effectiveness of different approaches for removing and recovering P from wastewater streams is important to reduce the overall impact of wastewater treatment. In this study, a process‐systems modelling framework for comprehensively evaluating these approaches in terms of both economic and environmental impacts is developed. Applying this framework, treatment pathways are designed, simulated and analysed to determine the most suitable approaches for P removal and recovery. The purpose of this methodology is not only to assist with plant design, but also to identify the principal economic and environmental factors acting as barriers to implementing a given technology, incorporating the impact of waste recovery. The results suggest that the chemical and ion‐exchange approaches studied deliver sustainable advantages over biological pathways, both economically and environmentally, with each possessing different strengths. The assessment methodology developed enables a more rational and environmentally sound wastewater plant design approach to be taken.